Contact mechanics analysis of a soft robotic fingerpad - Achilli, Gabriele Maria; Logozzo, Silvia; Malvezzi, Monica; Valigi, Maria Cristina (Frontiers in Mechanical Engineering, 2022)
The precision grasping capabilities of robotic hands is a key feature which is more and more required in the manipulation of objects in several unstructured fields, as for instance industrial, medical, agriculture and food industry. For this purpose, the realization of soft robotic fingers is crucial to reproduce the human finger skills. From this point of view the fingerpad is the part which is mostly involved in the contact. Particular attention must be paid to the knowledge of the mechanical contact behavior of soft artificial fingerpads. In this paper, artificial silicone fingerpads are applied to the last phalanx of robotic fingers actuated by tendons. The mechanical interaction between the fingerpad and a flat surface is analyzed in terms of deformations, contact areas and indentations. A reliable model of fingertip deformation properties provides important information for understanding robotic hand performance, that can be useful both in the design phase and for defining control strategies. The approach is based on theoretical, experimental, and numerical methods. The results will be exploited for the design of more effective robotic fingers for precision grasping of soft or fragile objects avoiding damages.